The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/jof6030127
|View full text |Cite
|
Sign up to set email alerts
|

Blue Light Induced Edible Mushroom (Lentinula edodes) Proteomic Analysis

Abstract: Blue light is an important environmental factor that induces mushroom growth and morphological changes. In this study, after confirming the morphological difference between Lentinula edodes (LE) under blue light condition (BL) and lightless condition (LL), the increase and decrease in LE protein and the expression of RNA of each protein were confirmed under each condition. LE specimens grown in BL and LL were identified by 253 spots in BL through 2D electrophoresis and LC-MSMS analysis, and 22 types of protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…Light is one of the most important environmental factors affecting the growth and development of almost all organisms. Previous studies have shown that appropriate light treatments can promote the fruiting body production of mushrooms (Kim et al 2014 ; Yang et al 2017 ; Wang et al 2020 ) and change the shape of fruiting body of mushrooms (Park and Jang 2020 ), however, the mechanism underlying blue light response of mushroom remains incompletely understood. The present study also displayed that blue light treatment promoted growth and pigmentation of fruiting bodies of F. filiformis .…”
Section: Discussionmentioning
confidence: 99%
“…Light is one of the most important environmental factors affecting the growth and development of almost all organisms. Previous studies have shown that appropriate light treatments can promote the fruiting body production of mushrooms (Kim et al 2014 ; Yang et al 2017 ; Wang et al 2020 ) and change the shape of fruiting body of mushrooms (Park and Jang 2020 ), however, the mechanism underlying blue light response of mushroom remains incompletely understood. The present study also displayed that blue light treatment promoted growth and pigmentation of fruiting bodies of F. filiformis .…”
Section: Discussionmentioning
confidence: 99%
“…Except for the 20S proteasome subunit protein, the other 5 proteins are down-regulated. 25 Proteasome as a multi-subunit protease is described as a large protein complex which is responsible for degrading intracellular proteins by using metabolic energy. Degradation of protein through the 26S ubiquitinproteasome system is reported as the main function of the proteasome.…”
Section: Discussionmentioning
confidence: 99%
“…Lentinula edodes is a mushroom used for food in northeast Asia. According to the report of Park and Jang, 25 the protein expression of samples that are radiated by 300 lux of blue light is compared with the samples in the absence of blue light (as controls). As it is described in this report, blue light radiation led to the dysregulation of 22 proteins (including 14 down-regulated and 8 upregulated individuals) in L. edodes.…”
Section: Methodsmentioning
confidence: 99%
“…Environmental factors such as nutrients, temperature, carbon dioxide concentration, and light are crucial for the growth of mushroom-forming fungi. Specifically, light plays a significant role in regulating the growth, development, and metabolism of mushrooms as an environment signal, and factors such as light intensity and wavelength are particularly important. Therefore, providing proper light conditions is essential for the induction and development of fruiting bodies. The effect of light has been investigated in various mushrooms, including Coprinopsis cinerea, Inonotus rheades, Lentinula edodes, Pleurotus ostreatus, , Pleurotus eryngii, Cerrena unicolor, and Hypsizygus marmoreus. , Studies have shown that different light qualities have varying effects on the growth of mycelium and the development of primordia or fruiting bodies . For example, although most mushrooms do not require light during the mycelial growth stage, the mycelia of Cordyceps militaris exposed to white light exhibit significantly faster growth compared to those kept in the dark.…”
Section: Introductionmentioning
confidence: 99%
“…27 Previous studies have indicated that ultraviolet and blue light are effective wavelengths for inducing fruiting bodies. 1 Specifically, blue light produces fruiting bodies with superior characteristics compared to other wavelengths, making it a commonly used light source to cultivate L. edodes 15 and H. marmoreus. 24,25 However, white light is generally used for most mushrooms, including oyster mushrooms, considering its effectiveness and convenience.…”
Section: ■ Introductionmentioning
confidence: 99%